(NsO^INENIQ(B: (NpXESY (B[1878-1888] /s (N~ASTX (B11s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B:s (NnAUKA(B,s, 1978)
(Nw (B11 (NTOM SOBRANIQ SO^INENIJ a(B.(Np(B. (N~EHOWA WO[LI PXESY(B, (NNAPISANNYE (B1878-1888 (NGG(B.s
rus
Keywords: (NpXESYs